The P300 Auditory Event-Related Potential May Predict Segregation of Competing Speech by Bimodal Cochlear Implant Listeners - Tao, Duo-Duo; Zhang, Yun-Mei; Liu, Hui; Zhang, Wen; Xu, Min; Galvin, John J.; Zhang, Dan; Liu, Ji-Sheng (Frontiers in Neuroscience, 2022)
Compared to normal-hearing (NH) listeners, cochlear implant (CI) listeners have greater difficulty segregating competing speech. Neurophysiological studies have largely investigated the neural foundations for CI listeners’ speech recognition in quiet, mainly using the P300 component of event-related potentials (ERPs). P300 is closely related to cognitive processes involving auditory discrimination, selective attention, and working memory. Different from speech perception in quiet, little is known about the neurophysiological foundations for segregation of competing speech by CI listeners. In this study, ERPs were measured for a 1 kHz vs. 2 kHz contrast in 11 Mandarin-speaking bimodal CI listeners and 11 NH listeners. Speech reception thresholds (SRTs) for a male target talker were measured in steady noise or with a male or female masker. Results showed that P300 amplitudes were significantly larger and latencies were significantly shorter for the NH than for the CI group. Similarly, SRTs were significantly better for the NH than for the CI group. Across all participants, P300 amplitude was significantly correlated with SRTs in steady noise (r = -0.65, p = 0.001) and with the competing male (r = -0.62, p = 0.002) and female maskers (r = -0.60, p = 0.003). Within the CI group, there was a significant correlation between P300 amplitude and SRTs with the male masker (r = -0.78, p = 0.005), which produced the most informational masking. The results suggest that P300 amplitude may be a clinically useful neural correlate of central auditory processing capabilities (e.g., susceptibility to informational masking) in bimodal CI patients.